12. Riluzole exerts short-term effects on cortical hyperexcitability in sporadic ALS. Issue 3 (March 2016) - Geevasinga, Nimeshan; Menon, Parvathi; Ng, Karl; Kiernan, Matthew C.; Vucic, Steve
Abstract : Objectives: Riluzole is the only neuroprotective agent to date shown to be effective in amyotrophic lateral sclerosis (ALS). The mechanism by which riluzole exerts neuroprotective effects in is via antagonism of glutamate, and recent studies in ALS patients have established partial normalization of cortical hyperexcitability. Given the modest therapeutic benefits, the duration of riluzoles effect in ALS is probably short, although this remains to be fully elucidated. Consequently, the present study assessed longitudinal effects of riluzole on cortical excitability in a cohort of sporadic ALS patients, by utilising threshold tracking transcranial magnetic stimulation (TTTMS). Methods: Studies were longitudinally undertaken on 18 sporadic ALS patients, with cortical excitability assessed at baseline (prior to initiation of riluzole), at 4, 8, and 12 weeks post riluzole initiation. Motor evoked potentials were recorded over the right abductor pollicis brevis muscle. Statistical analysis was undertaken with a Wilcoxson paired analysis, using a Bonferroni correction. Results: At baseline, cortical hyperexcitability was evident in the sporadic ALS cohort, as indicated by a marked reduction in SICI (3.5%). Riluzole therapy resulted in a marked increase in SICI at 4 weeks (8.4SEM%, P < 0.01), which was maintained at 8 weeks (9.4% SEM). Interestingly, at 12 weeks, SICI again reduced to baseline values (SICI12 week 4.6%) despite ongoing riluzole therapy. There were no significant changes in other TTMS parameters such as resting motor threshold, motor evoked potential amplitude or cortical silent period duration. Conclusion: The findings in the present study indicated that riluzole normalizes cortical excitability in ALS, although this cortical effect is limited. Given that cortical hyperexcitability is an important pathophysiological mechanism in ALS, the modest therapeutic benefits of riluzole could in part be explained by the short-term effects of riluzole on cortical hyperexcitability. Importantly, TTTMS may be utilised in future clinical trials to assess the effects of potential therapeutic agents on cortical function at early stages of drug development.